A relevância da informação como fator moderador da eficácia nos contratos : variações e reflexos nos contratos de seguros - Nery, Cláudio Lima (2015)
The information has an important role in the contemporary society. The development of capitalism has made relations massified, directly affecting the legal world, especially contracts. On the insurance contracts, the information is an essential element for the development of the contract. As a consequence, it is assumed that the information exchanged by the parties are always symmetrical, correct and clear, enabling the contractual balance. Otherwise, can destabilize the relationship, causing damages to the contract. Therefore, this research deals with the variation of information levels and its impacts on the insurance contracts. Based on the Brazilian legal system, including the fundamental rights of the Constitution, the Civil Code and the Consume Defense Code, it has performed the analysis of the relevance of information as a moderator factor of the effectiveness in insurance contracts, referring to the type of contract as a service available to the consumer. Reporting to decisions of the Brazilian Courts, it realizes that the requirement of the utmost good faith (uberrimae bona fidae) is an essential element of the insurance contratcs.